Einfluss der Schweißparameter auf das Ermüdungsverhalten hochfester Baustähle. Issue 11 (November 2013) - Horn, A.; Panzenböck, M.; Clemens, H.; Posch, G.
<x xml:space="preserve">Abstract</x> High strength low alloy steels are used in many different engineering areas. A commonly used joining technique for those steels is fusion welding. Generally, these components have to withstand fatigue due to dynamic loading. Using thermal joining techniques affect the mechanical properties of the steel. This study focuses on the influence of the heat input on the microstructure of high strength low alloy steels (S690). Furthermore, the fatigue behaviour with special regard to crack initiation and crack propagation is characterized.